2007
DOI: 10.1158/1535-7163.mct-07-0072
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cells with acquired antiestrogen resistance are sensitized to cisplatin-induced cell death

Abstract: Antiestrogens are currently used for treating breast cancer patients who have estrogen receptor -positive tumors. However, patients with advanced disease will eventually develop resistance to the drugs. Therefore, compounds effective on antiestrogen-resistant tumors will be of great importance for future breast cancer treatment. In this study, we have investigated the effect of the chemotherapeutic compound cisplatin using a panel of antiestrogenresistant breast cancer cell lines established from the human bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
4
14
1
Order By: Relevance
“…These observations were similar to those reported by Yde et al (29): MCF-7-derived anti-estrogen-resistant cells were more sensitive to cisplatin-induced cell death than the parental cells. The results from this study suggest that treatment with cisplatin or TRAIL alone induced cell death in 30-50% of Tam-resistant cells, however, the maximum effect is evident when these cells are treated with cisplatin plus TRAIL.…”
Section: Discussionsupporting
confidence: 92%
“…These observations were similar to those reported by Yde et al (29): MCF-7-derived anti-estrogen-resistant cells were more sensitive to cisplatin-induced cell death than the parental cells. The results from this study suggest that treatment with cisplatin or TRAIL alone induced cell death in 30-50% of Tam-resistant cells, however, the maximum effect is evident when these cells are treated with cisplatin plus TRAIL.…”
Section: Discussionsupporting
confidence: 92%
“…Increased levels of PKCα correlate to and can induce tamoxifen [38,39] and multidrug [9,10] resistance of ER-positive cell lines. In addition, overexpression of PKCα in MCF-7 cells leads to increased proliferation which is in line with our tumor data [4], but also make them more susceptible to apoptotic insults [40,41]. We found that the cell line with no detectable PKCα expression, T47D, had a lower percentage of Ki-67-positive cells and slower growth rate than the other cell lines, similar to the tumor data.…”
Section: Discussionsupporting
confidence: 90%
“…Many of these deaths are due to chemo-resistance, which is a common problem in the treatment of BrCa [12,13]. Cisplatin and its analogues have been widely used for treatment of human cancers, including advanced BrCa [14-16]. However, resistance to cisplatin represents a major obstacle in the effective management of metastatic BrCa [17].…”
Section: Discussionmentioning
confidence: 99%